Dysregulation of the Intestinal Microbiome in Patients With Haploinsufficiency of A20 - Toyofuku, Etsushi; Takeshita, Kozue; Ohnishi, Hidenori; Kiridoshi, Yuko; Masuoka, Hiroaki; Kadowaki, Tomonori; Nishikomori, Ryuta; Nishimura, Kenichi; Kobayashi, Chie; Ebato, Takasuke; Shigemura, Tomonari; Inoue, Yuzaburo; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction: Haploinsufficiency of A20 (HA20) is a form of inborn errors of immunity (IEI). IEIs are genetically occurring diseases, some of which cause intestinal dysbiosis. Due to the dysregulation of regulatory T cells (Tregs) observed in patients with HA20, gut dysbiosis was associated with Tregs in intestinal lamina propria. Methods: Stool samples were obtained from 16 patients with HA20 and 15 of their family members. Infant samples and/or samples with recent antibiotics use were excluded; hence, 26 samples from 13 patients and 13 family members were analyzed. The 16S sequencing process was conducted to assess the microbial composition of samples. Combined with clinical information, the relationship between the microbiome and the disease activity was statistically analyzed. Results: The composition of gut microbiota in patients with HA20 was disturbed compared with that in healthy family members. Age, disease severity, and use of immunosuppressants corresponded to dysbiosis. However, other explanatory factors, such as abdominal symptoms and probiotic treatment were not associated. The overall composition at the phylum level was stable, but some genera were significantly increased or decreased. Furthermore, among the seven operational taxonomic units (OTUs) that increased, two OTUs, Streptococcus mutans, and Lactobacillus salivarius considerably increased in patients with autoantibodies than those without autoantibodies. Discussion: Detailed interaction on intestinal epithelium remains unknown, the relationship between the disease and stool composition change helps us understand the mechanism of an immunological reaction to microorganisms.